Validation of a 3-h Sampling Interval to Assess Variability in Cytochrome P450 3A Phenotype and the Impact of Induction and Mechanism-Based Inhibition Using Midazolam as a Probe Substrate - van Dyk, Madelé; Kapetas, Asha J.; Hopkins, Ashley M.; Rodrigues, A. David; Vourvahis, Manoli; Sorich, Michael J.; Rowland, Andrew (Frontiers in Pharmacology, 2019)
Drug probe phenotyping is used extensively in academic and industry research to evaluate cytochrome P450 (CYP) phenotype in order to account for sources of between- and within- subject variability in metabolic clearance. In terms of application, CYP3A is the most important drug metabolising enzyme the most frequently studied. Currently, phenotyping studies for CYP3A involve the administration of midazolam and collection of timed blood samples up to 24-48 hours in order to determine an area under the plasma concentration time curve (AUC). The key challenge that limits the use of midazolam-based phenotyping for CYP3A in academic research settings and preclude the use of this approach in a clinical setting is the logistical burden of collecting frequent blood samples for up to 48 hrs post dose following the administration of a probe drug ± an interacting drug. The current study sought to validate if a reduced sampling interval could be used to accurately define both between-subject variability in CYP3A phenotype and the magnitude of changes in CYP3A activity due to either induction or mechanism-based inhibition. The area under the curve (AUC) for midazolam was assessed under baseline, induction (7 days rifampin, 300 mg daily) and, following a washout period of 4 days, mechanism based inhibition (3 days clarithromycin, 250 mg daily) conditions in a cohort of 30 health males. The capacity of normalised reduced sampling interval AUCs measured over 0 to 1 hr, 0 to 2 hr, 0 to 3hr and 0 to 4hr to accurately define the AUC0-6 was evaluated with respect to precision (R2 for correlation), bias (slope of normalised correlation), agreement (Bland Altman analysis) and proportional bias (linear regression of Bland Altman parameters). Robust concordance was observed between the AUC calculated from PK collection intervals of 0 to 3 hr and 0 to 6 hr in terms of both the measurement of between-subject variability in midazolam AUC and changes in midazolam AUC due to induction and mechanism-based inhibition of CYP3A4. On this basis, it is proposed that a 3-hr assessment of midazolam AUC represents a viable strategy to reduce the logistical burden associated with the assessment of CYP3A phenotype.